Utrecht-Management of Identity Commitments Scale: Validation in Spanish University Students - Llorent, Vicente J.; Álamo, Mercedes (Frontiers in Psychology, 2018)
The Utrecht-Management of Identity Commitments Scale (U-MICS) has already been validated in nine languages and has had a major scientific impact. Thus, the aim of this study was to validate this instrument in its Spanish version, one of the most important languages in the world. We analysed the psychometric properties of the scale, applied to a sample of 378 students of the Faculty of Education at the University of Cordoba. The scale consists of 13 items, divided into three dimensions of the process of identity: commitments, in-depth exploration and reconsideration of the commitments. In this report, the factorial three-dimensional model of process identity is confirmed and shows that the instrument is reliable for measuring the educational, social or global identity of the individual.